Bildungs- und Berufsberatung in der Migrationsgesellschaft Pädagogische Perspektiven auf Beratung zur Anerkennung im Ausland erworbener Qualifikationen - Schmidtke, Birgit (Pädagogik, 2020)
Recognition counselling as a support service for persons with qualifications acquired abroad is becoming increasingly important to society and is the same time confronted with legal and social contradictions. This dissertation offers a systematic description and justification of Recognition Counselling as a new form of Specialist Counselling service and shows how educational and vocational guidance can position itself and become more professional in the society of migration.